Analisis Semiotika Puisi “Kesabaran” Karya Chairil Anwar - Moch Ajhar Rodiulloh; Muhamad Rifaldi (Universitas Palan, 2023)
Literary work is a creation that is conveyed by speaking or communicative about the author's intention which aims for aesthetics. One example of a literary work is poetry, poetry is a type of literary work that has beautiful, animating, and deep meanings and meanings, the words and sentences contained in it mostly come from the heart of the creator of the poem, when reading it you also have to use a good intonation. clear, and expressions that match the content of the poem. This study aims to semiotically analyze the poem entitled